Solid-state electrolyte, preparation method thereof and solid-state lithium battery
By coating the oxide solid electrolyte with amorphous amorphous phase halide electrolyte and forming a tantalum-containing interface layer, the problem of high interface impedance in all-solid-state batteries is solved, the Coulomb efficiency and safety are improved, and the manufacturing cost is reduced.
Patent Information
- Application Number
- CN202510329182.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-20
AI Technical Summary
The mechanical strength and hardness of oxide electrolyte particles in existing all-solid state batteries lead to poor interface contact with the electrodes and the growth of lithium dendrites, resulting in high interface impedance and low Coulomb efficiency.
The oxide solid electrolyte is coated with an amorphous amorphous phase halide electrolyte and a tantalum-containing interface layer is formed on its surface. The compatibility and stability of the electrolyte are improved through ball milling and sintering processes.
The interface impedance of the oxide solid electrolyte is reduced, the Coulomb efficiency and safety of solid-state batteries are improved, and manufacturing costs are reduced.
Smart Images

Figure CN119852509A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium batteries, and in particular relates to a solid electrolyte and a preparation method thereof, and a solid lithium battery. Background Art
[0002] At present, the oxide electrolyte particles in all-solid-state batteries (ASSB) have high mechanical strength and hardness, resulting in very poor interface contact with the electrode, and the presence of lithium dendrite growth, leading to high interface impedance. The existing technology is to reduce the interface impedance by adding polymers to artificially form a solid electrolyte interface (SEI), resulting in low efficiency of high-rate charge and discharge of all-solid-state batteries; it reduces the charge and discharge efficiency of all-solid-state batteries and reduces the user experience.
[0003] The solid electrolytes in the prior art have the problems of poor contact and lithium dendrite growth, which results in high impedance at the electrode interface and low coulombic efficiency. Summary of the invention
[0004] The present application provides a solid electrolyte and a preparation method thereof and a solid lithium battery, aiming to solve to a certain extent the problem of poor contact of the solid electrolyte, growth of lithium dendrites resulting in high impedance at the electrode interface and low coulombic efficiency.
[0005] In a first aspect, the present application provides a solid electrolyte, the solid electrolyte comprising an amorphous amorphous halide electrolyte, an oxide solid electrolyte and a tantalum-containing interface layer, the amorphous amorphous halide electrolyte coating the oxide solid electrolyte, the tantalum-containing interface layer coating the surface of the solid electrolyte; the molecular formula of the solid electrolyte is TaM 5 -Li a X b Y c OCl@LLNO; Among them, Li a X b Y c OCl is an amorphous halide electrolyte, LLNO is an oxide solid electrolyte, and TaM 5 The tantalum-containing interface layer, M is iodine or fluorine, X is a first metal element, the first metal element is derived from a raw material halogenated metal salt, Y is a second metal element, the second metal element is derived from a raw material polymerized halogenated metal salt, N is zirconium and / or titanium, 1≦a≦2, 0≦b≦5, 0≦c≦5, and at least one of b and c is greater than 0.
[0006] In one embodiment, the first metal element includes one or more of aluminum, calcium, chromium, gallium, zinc, magnesium, and tungsten; The second metal element includes one or more of aluminum, calcium, chromium, copper, cobalt, tin, rhodium, vanadium, and iron; If the first metal element is the same as the second metal element, the value of b or c is 0.
[0007] In one embodiment, the oxide solid electrolyte includes a combination of one or more of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, and lithium lanthanum zirconium titanium oxide; The metal halide salt includes AlCl 3 , CaCl 2 CrCl 5 、GaCl 3 、ZnCl 2 MgCl 2 、WCl 5 A combination of one or more of the following; The polymeric halogenated metal salt includes AlCl 3 ·nH 2 O, CaCl 2 ·nH 2 O、CrCl 2 ·nH 2 O, CuCl 2 ·nH 2 O、CoCl 2 ·nH 2 O、SnCl 2 ·nH 2 O、RhCl 2 ·nH 2 O、VCl 2 ·nH 2 O, FeCl 2 ·nH 2 A combination of one or more of O, 1≦n≦6.
[0008] In a second aspect, the present application provides a method for preparing a solid electrolyte as described in any one of the first aspects, comprising: Mixing lithium chloride, a metal halide salt, and a polymerized metal halide salt according to a preset molar ratio, and adding the obtained halogenated mixture into a ball mill for ball milling; During the ball milling process, adding the oxide solid electrolyte multiple times at a first preset interval until the mass ratio of the oxide solid electrolyte to the halogenated mixture reaches a preset mass ratio, and the mass of the oxide solid electrolyte added each time is 5% to 15% of the mass of the halogenated mixture; During the ball milling process, the ball milling is stopped every second preset time interval, and the ball mill is kept warm at a preset temperature under an inert gas atmosphere to obtain an electrolyte powder; Pressing the electrolyte powder into a shape to obtain an electrolyte; Etching the electrolyte to a preset depth; The etched electrolyte and the water-absorbing molecular sieve are sintered in a tantalum-containing steam atmosphere in a tubular furnace to obtain a solid electrolyte in which an amorphous non-crystalline halide electrolyte covers the oxide solid electrolyte.
[0009] In one embodiment, the preset molar ratio of the lithium chloride, the metal halide salt, and the polymerized metal halide salt is (1-10): (1-20): 1; The ball-to-material ratio of the ball mill is (10~40) : 1, the ball milling time is 20 min~2400 min, and the ball milling speed is 1 r / min~1000 r / min.
[0010] In one embodiment, the first preset interval time is 10 min to 30 min; The preset mass ratio of the oxide solid electrolyte to the halogenated mixture is 10:(0.1-5); The D50 of the oxide solid electrolyte is 700 nm~1500 nm.
[0011] In one embodiment, the second preset interval time is 5 min to 10 min; The preset temperature is 100° C. to 300° C., and the insulation time of the inert gas insulation is 10 min to 60 min.
[0012] In one embodiment, the preset depth is 3 nm to 7 nm.
[0013] In one embodiment, the tantalum-containing vapor includes tantalum pentaiodide vapor or tantalum pentafluoride vapor; The sintering parameters are: sintering temperature is 400°C to 1200°C, and sintering time is 2 h to 24 h.
[0014] In a third aspect, the present application provides a solid-state lithium battery, comprising a solid-state electrolyte as described in any one of the first aspect, or a solid-state electrolyte obtained by the preparation method of a solid-state electrolyte sheet as described in any one of the second aspect.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The solid electrolyte provided in the present application is an amorphous non-crystalline halide electrolyte coated oxide solid electrolyte, and a tantalum-containing interface layer is coated on the surface of the solid electrolyte; the molecular formula of the solid electrolyte is TaM 5 -Li a X b Y c OCl@LLNO; among them, Li a Xb Y c OCl is an amorphous halide electrolyte, LLNO is an oxide solid electrolyte, and TaM 5 is a tantalum-containing interface layer, M is iodine or fluorine, X is a first metal element, the first metal element is derived from a raw material halogenated metal salt, Y is a second metal element, the second metal element is derived from a raw material polymerized halogenated metal salt, N is zirconium and / or titanium, 1≦a≦2, 0≦b≦5, 0≦c≦5, and at least one of b and c is greater than 0; when the amorphous non-crystalline halide electrolyte is synthesized with the oxide solid electrolyte, the byproduct HCl gas removes the impurities (such as Li 2 CO 3 、LiOH、Li 2 O), exposing the lithium-philic phase, improving the compatibility of the oxide solid electrolyte with the polymer electrolyte / binder, thereby reducing the interfacial impedance of the oxide solid electrolyte and improving the coulombic efficiency of the solid-state battery; when the oxide solid electrolyte forms lithium dendrites along the tantalum-containing interface layer, the amorphous amorphous halide electrolyte will react with the lithium dendrites to consume the lithium dendrites to form a self-healing phenomenon, avoiding the formation of dead lithium from lithium ions, further improving the coulombic efficiency, and also improving the safety of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 is a schematic structural diagram of a solid electrolyte provided in one embodiment of the present application; Figure 2 is a particle element distribution diagram of the halogenated mixture of the amorphous non-crystalline halide electrolyte raw material and the oxide solid electrolyte after ball milling in step 2 of Example 1 of the present application; Figure 3 The amorphous non-crystalline halide electrolyte LiAl of Example 1 of the present application 1.5 OCl 3.5 Schematic diagram comparing the concentration of HCl produced by the combined reaction of LAOC (abbreviated as LAOC) and the oxide solid electrolyte LLZO and the reaction of LAOC alone; Figure 4 Schematic diagram comparing the electrolyte impedance of the co-milling synthesis reaction of LAOC and LLZO in Example 1 of the present application with the electrolyte impedance of the initial LLZO particles; Figure 5It is a schematic diagram of the impedance of the solid electrolyte prepared by using tantalum pentaiodide vapor in Example 1 of the present application and using an argon atmosphere of an inert gas without using tantalum pentaiodide vapor in Comparative Example 8; Figure 6 It is a schematic diagram of the Li / SE / Li symmetric battery cycle assembled with solid electrolytes prepared in Example 1, Comparative Example 8, and Comparative Example 9 of the present application; Figure 7 It is a schematic diagram comparing the capacity retention rates of all-solid-state batteries assembled with solid electrolyte sheets prepared in Example 2 and Comparative Example 6 of the present application, respectively. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0019] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0020] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.
[0021] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0022] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0023] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0024] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0025] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0027] At present, lithium-ion batteries have been developed and widely used as an electrochemical energy storage device, and they play an important role in powering portable electronic devices.
[0028] However, lithium-ion batteries still have outstanding safety issues in terms of inherent flammability and potential thermal runaway, especially when exposed to high temperatures or physical damage. In addition, the growing demand for large-scale energy storage solutions, especially the integration of renewable energy and electric drive technology for electric vehicles, has increased the demand for batteries with higher energy density, higher safety and more sustainable materials. The existing lithium-ion batteries cannot meet the needs of scenario development in terms of energy density and other aspects.
[0029] The all-solid-state battery (ASSB), a new generation of battery technology, has many advantages over traditional lithium-ion batteries, such as electrochemical energy storage and power supply, but also includes higher safety, higher energy density, higher thermal stability and longer service life.
[0030] However, the oxide electrolyte particles in the current all-solid-state battery have high mechanical strength and hardness, resulting in very poor interface contact with the electrode, and the presence of lithium dendrite growth, leading to high interface impedance. The existing technology is to reduce the interface impedance by adding polymers to artificially form a solid electrolyte interface (SEI, Solid Electrolyte Interface) and other means, resulting in low efficiency of high-rate charge and discharge of all-solid-state batteries; it reduces the charge and discharge efficiency of all-solid-state batteries and reduces the user experience.
[0031] In order to solve the above problems to a certain extent, the present application provides a solid electrolyte in the first aspect, such as Figure 1 As shown, the solid electrolyte includes an amorphous amorphous halide electrolyte, an oxide solid electrolyte and a tantalum-containing interface layer. The amorphous amorphous halide electrolyte covers the oxide solid electrolyte, and the tantalum-containing interface layer 2 covers the surface of the solid electrolyte 1; the molecular formula of the solid electrolyte is TaM 5 -Li a X b Y c OCl@LLNO; the enlarged image is a schematic diagram of an amorphous halide electrolyte coated with an oxide solid electrolyte, Li a X b Y c OCl is an amorphous halide electrolyte, LLNO is an oxide solid electrolyte, and TaM 5 It is a tantalum-containing interface layer, M is iodine or fluorine, X is a first metal element, the first metal element is derived from a raw material halogenated metal salt, Y is a second metal element, the first metal element is derived from a raw material polymerized halogenated metal salt, N is zirconium and / or titanium, 1≦a≦2, 0≦b≦5, 0≦c≦5, and at least one of b and c is greater than 0.
[0032] In this embodiment, when the amorphous non-crystalline halide electrolyte is synthesized with the oxide solid electrolyte, the by-product HCl gas removes the impurities (such as Li 2 CO 3 、LiOH、Li 2O), exposing the lithium-philic phase, improving the compatibility of the oxide solid electrolyte with the polymer electrolyte / binder, thereby reducing the interface impedance of the oxide solid electrolyte, enabling high-rate charge and discharge, and improving the coulombic efficiency of the solid-state battery; and when the oxide solid electrolyte grows lithium dendrites along the tantalum-containing interface layer, the amorphous amorphous halide electrolyte will react with the lithium dendrites to consume the lithium dendrites to form a self-healing phenomenon, avoiding the formation of dead lithium by lithium ions, further improving the coulombic efficiency, and also improving the safety of the solid-state battery. In addition, without affecting the ionic conductivity of the oxide solid electrolyte, the tantalum-containing interface layer secondary coats the oxide solid electrolyte, avoiding the reaction between the halide electrolyte coating layer and the lithium metal negative electrode, obtaining a dual-stable interface phase for the positive and negative electrodes, improving the stability of the lithium metal negative electrode, and further improving the safety of the solid-state battery.
[0033] In one embodiment, the metal halide salt comprises AlCl 3 , CaCl 2 CrCl 5 、GaCl 3 、ZnCl 2 MgCl 2 、WCl 5 The first metal element includes one or more of aluminum, calcium, chromium, gallium, zinc, magnesium, and tungsten; the halide metal salt can be coated in an amorphous form at the grain boundary of the oxide solid electrolyte, can block electron migration without affecting ion transport, and inhibit the growth of lithium dendrites.
[0034] In one embodiment, the polymeric halide metal salt comprises AlCl 3 ·nH 2 O, CaCl 2 ·nH 2 O、CrCl 2 ·nH 2 O, CuCl 2 ·nH 2 O、CoCl 2 ·nH 2 O、SnCl 2 ·nH 2 O、RhCl 2 ·nH 2 O、VCl 2 ·nH 2 O, FeCl 2 ·nH 2 O, 1≦n≦6; the second metal element includes one or more of aluminum, calcium, chromium, copper, cobalt, tin, rhodium, vanadium, and iron. If the first metal element is the same as the second metal element, Li a X bY c The value of b or c in OCl is 0. For example, if the first metal element and the second metal element are both Al, then Li a X b Y c OCl represents Li a Al b OCl or Li a Al c OCl; The polymerized metal halide salt can be coated in an amorphous form at the grain boundary of the oxide solid electrolyte, which can block electron migration without affecting ion transport and inhibit the growth of lithium dendrites; in addition, the polymerized metal halide salt will also hydrolyze and generate HCl gas, which can remove impurities on the surface of the oxide solid electrolyte (such as Li 2 CO 3 、LiOH、Li 2 O), exposing the lithium-philic phase, improving the compatibility of the oxide solid electrolyte with the polymer electrolyte / binder, thereby reducing the interfacial impedance of the oxide solid electrolyte and improving the coulombic efficiency of the solid-state battery.
[0035] In one embodiment, N is zirconium and titanium, zirconium, or titanium, that is, the oxide solid electrolyte LLNO includes a combination of one or more of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), and lithium lanthanum zirconium titanium oxide (LLZTO); the oxide solid electrolyte of this embodiment has a high ionic conductivity (reaching 10 -3 S / cm level), and has high chemical and electrochemical stability with the lithium metal negative electrode.
[0036] In a second aspect, the present application provides a method for preparing a solid electrolyte as described in any one of the first aspects, comprising: S10, mixing lithium chloride, a halogenated metal salt, and a polymerized halogenated metal salt according to a preset molar ratio, and adding the obtained halogenated mixture into a ball mill for ball milling.
[0037] S20, during the ball milling process, adding the oxide solid electrolyte multiple times at a first preset interval time until the mass ratio of the oxide solid electrolyte to the halogenated mixture reaches a preset mass ratio, and the mass of the oxide solid electrolyte added each time is 5% to 15% of the mass of the halogenated mixture.
[0038] S30, during the ball milling process, the ball milling is suspended after every second preset interval, and the ball mill is kept warm at a preset temperature under an inert gas atmosphere to obtain an electrolyte powder.
[0039] S40, pressing the electrolyte powder into a shape to obtain an electrolyte.
[0040] S50, etching the electrolyte to a preset depth.
[0041] S60, sintering the etched electrolyte and the water-absorbing molecular sieve in a tubular furnace in a tantalum-containing steam atmosphere to obtain a solid electrolyte of an amorphous non-crystalline halide electrolyte coated with an oxide solid electrolyte.
[0042] The solid electrolyte particles obtained by the prior art preparation method have high mechanical strength and hardness, and the oxide solid electrolyte is easy to produce LiOH in the oil-based solvent, and LiOH will cause the binder / polymer to denature, so the oxide solid electrolyte is not suitable as an inorganic filler for the polymer; the interface contact between the solid electrolyte and the electrode is very poor, resulting in high interface impedance. In addition, the preparation method of the solid electrolyte in the prior art adopts a complex hot pressing and sintering method to prepare the electrolyte layer, which increases the manufacturing cost.
[0043] The solid electrolyte obtained by the preparation method of the solid electrolyte of this embodiment has an amorphous non-crystalline halide electrolyte Li a X b Y c When OCl is synthesized by ball milling, vacuum heating and heat preservation with oxide solid electrolyte, the polymerized halide metal salt will hydrolyze and react to generate HCl gas. The byproduct HCl gas will remove the impurities on the surface of the oxide solid electrolyte (such as Li 2 CO 3 、LiOH、Li 2 O), exposing the lithium-philic phase, improving the compatibility of the oxide solid electrolyte with the polymer electrolyte / binder, thereby reducing the interface impedance of the oxide solid electrolyte, enabling high-rate charge and discharge, and improving the coulomb efficiency of the solid-state battery; and when the oxide solid electrolyte grows lithium dendrites along the tantalum-containing interface layer, the amorphous amorphous halide electrolyte will react with the lithium dendrites to consume the lithium dendrites to form a self-healing phenomenon, avoiding the formation of dead lithium by lithium ions, further improving the coulomb efficiency, and also improving the safety of the solid-state battery. In addition, without affecting the ionic conductivity of the oxide solid electrolyte, the tantalum-containing interface layer performs a secondary coating surface treatment on the oxide solid electrolyte, avoiding the reaction between the halide electrolyte coating layer and the lithium metal negative electrode, obtaining a dual-stable interface phase for the positive and negative electrodes, improving the stability of the lithium metal negative electrode, and further improving the safety of the solid-state battery. At the same time, this embodiment uses a cold pressing method to prepare the electrolyte layer, uses a polymerized halide metal salt with crystal water to introduce oxygen atoms, does not use battery-grade raw materials, and further reduces the cost of the solid-state battery.
[0044] In one embodiment, the solid electrolyte is in the shape of a sheet or a cake, wherein the thickness of the solid electrolyte is 20 μm to 150 μm. a X b Yc The ionic conductivity of OCl is also 10 -3 S / cm level, and the texture is relatively soft. When pressed, it can fill the gaps between the oxide solid electrolyte particles, improve the compaction density, and form a sheet or cake-shaped solid electrolyte with few gaps and high density, thereby improving the energy density of the solid-state battery.
[0045] In one embodiment, the preset molar ratio of lithium chloride, metal halide salt, and polymerized metal halide salt is (1-10):(1-20):1. The molar ratio range of this embodiment can avoid the generation of more HCl gas and reduce the processing cost. It can also maintain the balance between lithium and metal salt and improve the ionic conductivity of the solid-state battery.
[0046] In one embodiment, the ball-to-material ratio of ball milling is (10-40):1, the ball milling time is 20 min-2400 min, and the ball milling rate is 1 r / min-1000 r / min. The ball milling parameters of this embodiment can better mix the halide electrolyte and the oxide solid electrolyte and obtain a particle size that meets the requirements.
[0047] In one embodiment, the first preset interval time is 10 min~30 min; the preset mass ratio of the oxide solid electrolyte to the halogenated mixture is 10:(0.1~5); the D50 of the oxide solid electrolyte is 700 nm~1500 nm; the first preset interval time of this embodiment can make the halide electrolyte and the oxide solid electrolyte mix better and improve the coverage rate; and the mass of the oxide solid electrolyte is greater than the mass of the halogenated mixture, which ensures the electrochemical performance of the solid-state battery; maintaining the D50 particle size of the oxide solid electrolyte can increase the contact area, thereby reducing the interface impedance.
[0048] In one embodiment, the second preset interval time is 5 min to 10 min; the preset temperature is 100°C to 300°C, and the insulation time of the inert gas is 10 min to 60 min; the insulation temperature and time of this embodiment can allow the polymerized halide metal salt to be completely hydrolyzed and the generated HCl gas to react completely, so as to better remove the impurities on the surface of the oxide solid electrolyte.
[0049] In one embodiment, the preset depth is 3 nm to 7 nm. In this embodiment, a preset depth is etched on the electrolyte surface through an etching process, thereby removing the impurities formed on the electrolyte surface due to ball milling and tableting, so that the tantalum-containing vapor and the halide electrolyte form a good interface phase, making the interface phase more compact.
[0050] In one embodiment, the tantalum-containing vapor includes tantalum pentaiodide vapor or tantalum pentafluoride vapor; the sintering parameters are: sintering temperature is 400°C~1200°C, and sintering time is 2 h~24 h; the introduction of tantalum-containing vapor can prevent the reaction between the halide electrolyte coating and the lithium metal negative electrode, thereby improving the stability of the lithium metal negative electrode.
[0051] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.
[0052] Example 1 A method for preparing a solid electrolyte, comprising: Step 1: LiCl, AlCl 3 (metal halide salt), AlCl 3 ·5H 2 O (polymerized halide metal salt) in a molar ratio of 6:8:1, and the obtained halogenated mixture is added into a ball mill for light mixing and ball milling. The ball mill is made of agate, the ball-to-material ratio is 20:1, the ball milling time is 360 min, and the ball milling speed is 50 r / min.
[0053] Step 2. During the ball milling process, the oxide solid electrolyte is added multiple times at intervals of 20 minutes until the mass ratio of the oxide solid electrolyte to the halogenated mixture reaches a mass ratio of 10:0.5. The mass of the oxide solid electrolyte added each time is 10% of the mass of the halogenated mixture. The D50 of the oxide solid electrolyte is 700 nm. The oxide solid electrolyte is a lithium lanthanum zirconium oxide (LLZO) electrolyte.
[0054] Step 3: While continuing the ball milling, allow the oxide solid electrolyte and the halogenated mixture to be fully mixed, suspend the ball milling every 20 minutes, and place the ball mill in a vacuum oven under an inert gas atmosphere at 260° C. to obtain electrolyte powder for 30 minutes.
[0055] Step 4: Pressing the electrolyte powder into a sheet in a tableting mold to obtain an electrolyte sheet.
[0056] Step 5, placing the electrolyte sheet into an etcher, and etching the surface of the electrolyte sheet to a depth of 7 nm.
[0057] Step 6, placing the etched electrolyte sheet into a crucible with a water-absorbing molecular sieve, the particles of the water-absorbing molecular sieve cover the electrolyte sheet, and placing the crucible in a tubular furnace in a tantalum pentaiodide vapor atmosphere for sintering to obtain an amorphous amorphous phase halide electrolyte coated oxide solid electrolyte. The sintering temperature is 700°C, the sintering time is 10 h, and the molecular formula of the solid electrolyte is TaI 5 -LiAl 1.5 OCl 3.5@LLZO.
[0058] Figure 2 This is the particle element distribution diagram of the halogenated mixture of the amorphous amorphous halide electrolyte raw material and the oxide solid electrolyte after ball milling in step 2 of Example 1; wherein most of the aluminum element covers the surface of the oxide solid electrolyte, indicating that the amorphous amorphous halide electrolyte covers the oxide solid electrolyte.
[0059] Figure 3 The amorphous non-crystalline halide electrolyte LiAl of Example 1 1.5 OCl 3.5 Schematic diagram of the comparison of HCl concentrations between the synthesis of HCl produced by the combined reaction of LAOC (abbreviated as LAOC) and the oxide solid electrolyte LLZO and the synthesis of HCl produced by the reaction of LAOC alone; Figure 3 As shown, since the concentration of HCl synthesized by the co-reaction of LAOC and LLZO is lower than that of HCl synthesized by LAOC alone, it means that the HCl synthesized by the co-reaction of LAOC and LLZO can remove the oxide impurities on the surface of LLZO particles.
[0060] Figure 4 Schematic diagram showing the comparison of the electrolyte impedance of the co-milling synthesis reaction of LAOC and LLZO in Example 1 and the electrolyte impedance of the initial LLZO particles, as shown in FIG. Figure 4 As shown, the electrolyte impedance of the co-synthesis reaction of LAOC and LLZO in Example 1 is lower than that of LLZO, indicating that after the chloride electrolyte removes the oxide impurities on the surface of the LLZO particles and LAOC coats LLZO, the elastic modulus of the oxide electrolyte is reduced, thereby improving the ionic conductivity of the solid electrolyte.
[0061] Example 2: The difference from Example 1 is that the raw material of amorphous non-crystalline halide electrolyte is added, and some process parameters are changed; A method for preparing a solid electrolyte, comprising: Step 1: LiCl, AlCl 3 (metal halide), RhCl 3 ·5H 2 O (polymeric metal halide), VCl 3 ·5H 2 O (polymerized halide metal salt) is mixed in a molar ratio of 9:14:0.5:0.5, and the obtained halogenated mixture is added into a ball mill for light mixing and ball milling. The ball mill is made of agate, the ball-to-material ratio is 40:1, the ball milling time is 540 min, and the ball milling rate is 300 r / min.
[0062] Step 2. During the ball milling process, the oxide solid electrolyte is added multiple times at intervals of 30 minutes until the mass ratio of the oxide solid electrolyte to the halogenated mixture reaches a mass ratio of 10:2. The mass of the oxide solid electrolyte added each time is 10% of the mass of the halogenated mixture. The D50 of the oxide solid electrolyte is 1500 nm. The oxide solid electrolyte is a lithium lanthanum titanium oxide (LLTO) electrolyte.
[0063] Step 3: While continuing the ball milling, allow the oxide solid electrolyte and the halogenated mixture to be fully mixed, suspend the ball milling every 20 minutes, and place the ball mill in a vacuum oven under an inert gas atmosphere at 260° C. to obtain electrolyte powder for 30 minutes.
[0064] Step 4: Pressing the electrolyte powder into a sheet in a tableting mold to obtain an electrolyte sheet.
[0065] Step 5, placing the electrolyte sheet into an etcher, and etching the surface of the electrolyte sheet to a depth of 3 nm.
[0066] Step 6: Place the etched electrolyte sheet into a crucible with a water-absorbing molecular sieve, the particles of the water-absorbing molecular sieve cover the electrolyte sheet, and place the crucible in a tubular furnace in a tantalum pentafluoride vapor atmosphere for sintering to obtain an amorphous amorphous phase halide electrolyte coated oxide solid electrolyte solid electrolyte, the molecular formula of the solid electrolyte is TaF 5 -Li 1.5 Al 1.25 R 0.625 V 0.625 OCl 7 @LLTO, sintering temperature is 700℃ and sintering time is 10 h.
[0067] Example 3: The difference from Example 1 is that the raw material of amorphous non-crystalline halide electrolyte is added, and some process parameters are changed; A method for preparing a solid electrolyte, comprising: Step 1: LiCl, CaCl 3 (metal halide salt), AlCl 3 ·5H 2 O (polymerized halide metal salt) is mixed in a molar ratio of 6:11:1, and the obtained halogenated mixture is added into a ball mill for light mixing and ball milling. The ball mill is made of agate, the ball-to-material ratio is 35:1, the ball milling time is 280min, and the ball milling speed is 250 r / min.
[0068] Step 2. During the ball milling process, the oxide solid electrolyte is added several times at intervals of 60 minutes until the mass ratio of the oxide solid electrolyte to the halogenated mixture reaches a mass ratio of 10:0.15, and the mass of the oxide solid electrolyte added each time is 10% of the mass of the halogenated mixture. The oxide solid electrolyte is a lithium lanthanum titanium oxide (LLTO) electrolyte and a lithium lanthanum zirconium oxide (LLZO) electrolyte. The D50 of the oxide solid electrolyte is 1000 nm, and the mass ratio of the lithium lanthanum titanium oxide (LLTO) electrolyte and the lithium lanthanum zirconium oxide (LLZO) electrolyte is 0.45:0.55.
[0069] Step 3: While continuing the ball milling, allow the oxide solid electrolyte and the halogenated mixture to be fully mixed, suspend the ball milling every 20 minutes, and place the ball mill in a vacuum oven under an inert gas atmosphere at 260° C. to obtain electrolyte powder for 30 minutes.
[0070] Step 4: Pressing the electrolyte powder into a sheet in a tableting mold to obtain an electrolyte sheet.
[0071] Step 5, placing the electrolyte sheet into an etcher, and etching the surface of the electrolyte sheet to a depth of 5 nm.
[0072] Step 6, placing the etched electrolyte sheet into a crucible with a water-absorbing molecular sieve, the particles of the water-absorbing molecular sieve cover the electrolyte sheet, and placing the crucible in a tubular furnace in a tantalum-containing vapor atmosphere for sintering to obtain an amorphous amorphous phase halide electrolyte coated oxide solid electrolyte solid electrolyte, the molecular formula of the solid electrolyte is TaI 5 / TaF 5 -LiCa 1.83 Al 0.17 OCl 5 @LLTO-LLZO, the sintering temperature is 700℃, the sintering time is 10 h, the tantalum-containing vapor is tantalum pentaiodide vapor and tantalum pentafluoride vapor, and the mass ratio of tantalum pentaiodide to tantalum pentafluoride is 5:95.
[0073] Comparative Example 1 is different from Example 1 in that the raw materials of the amorphous non-crystalline halide electrolyte do not include AlCl 3 (metal halide salt).
[0074] Comparative Example 2 is different from Example 1 in that the raw materials of the amorphous non-crystalline halide electrolyte do not include AlCl 3 ·5H 2 O (polymeric metal halide).
[0075] Comparative Example 3 is different from Example 1 in that lithium chloride LiCl, AlCl 3 (metal halide salt), AlCl 3 ·5H2 The molar ratio of O (polymeric halide metal salt) is 11:21:1.
[0076] Comparative Example 4 is different from Example 2 in that the mass ratio of the oxide solid electrolyte to the halogenated mixture is 1:1.
[0077] Comparative Example 5 is different from Example 2 in that the oxide solid electrolyte is lithium aluminum titanium phosphate.
[0078] Comparative Example 6 is different from Example 2 in that the D50 of the oxide solid electrolyte is 300 nm.
[0079] Comparative Example 7 is different from Example 3 in that the tableting in step 4 and the etching in step 5 are not included, and the electrolyte powder is sintered according to step 6.
[0080] Comparative Example 8 is different from Example 3 in that step 6 does not use a tantalum-containing vapor atmosphere, but an inert gas argon atmosphere.
[0081] Comparative Example 9 is different from Example 3 in that the sintering temperature in step 6 is 200°C.
[0082] Data testing: The electrolyte sheets obtained in Examples 1 to 3 and Comparative Examples 1 to 9 were assembled into an all-solid-state battery, with NCM811 as the active material for the positive electrode, polyvinylidene fluoride (PVDF) as the binder, superP as the conductive agent, and lithium metal foil with a thickness of 20 um for the negative electrode. The batteries were assembled in a mold with an assembly pressure of 5 MPa. The charge and discharge cycle test was performed at 45°C with a rate of 0.33C charging and 0.33C discharging, and coulombic efficiency = (discharge capacity / charge capacity) × 100%. The coulombic efficiency and capacity retention rate of the charge and discharge cycles of each embodiment and each comparative example were obtained, as shown in Table 1.
[0083]
[0084] As shown in Table 1, the coulombic efficiency and capacity retention rate of the solid-state batteries corresponding to the solid-state electrolytes prepared in Examples 1 to 3 are significantly higher than those of the comparative examples.
[0085] Figure 5 Schematic diagrams of the impedance of solid electrolytes prepared in Example 1 using tantalum pentaiodide vapor and in Comparative Example 8 using an inert gas argon atmosphere without using tantalum pentaiodide vapor.
[0086] Figure 6 Schematic diagram of the Li / SE / Li symmetric battery cycle assembled with solid electrolytes prepared in Example 1, Comparative Example 8, and Comparative Example 9. The voltage stability of the electrolyte sheet of Example 1 to lithium metal is much higher than that of the electrolyte sheets of Comparative Examples 8 and 9 to lithium metal.
[0087] Figure 7 Schematic diagram comparing the capacity retention rates of all-solid-state batteries assembled with solid electrolyte sheets prepared in Example 2 and Comparative Example 6, respectively; indicating that the D50 particles of the solid electrolyte need to be maintained within a certain range, as exceeding the range will cause the electrochemical performance of the solid-state battery to deteriorate.
[0088] It should be understood that the size of the serial numbers of the steps in the above embodiments does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0089] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0090] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A solid electrolyte, characterized in that The solid electrolyte comprises an amorphous non-crystalline halide electrolyte, an oxide solid electrolyte and a tantalum-containing interface layer, wherein the amorphous non-crystalline halide electrolyte covers the oxide solid electrolyte, and the tantalum-containing interface layer covers the surface of the solid electrolyte; The molecular formula of the solid electrolyte is TaM5-Li a X b Y c OCl@LLNO; Among them, Li a X b Y c OCl is the amorphous non-crystalline halide electrolyte, LLNO is the oxide solid electrolyte, TaM5 is the tantalum-containing interface layer, M is iodine or fluorine, X is a first metal element, the first metal element is derived from a raw material halogenated metal salt, Y is a second metal element, the second metal element is derived from a raw material polymerized halogenated metal salt, N is zirconium and / or titanium, 1≦a≦2, 0≦b≦5, 0≦c≦5, and at least one of b and c is greater than 0.
2. The solid electrolyte according to claim 1, characterized in that The first metal element includes one or more of aluminum, calcium, chromium, gallium, zinc, magnesium, and tungsten; The second metal element includes one or more of aluminum, calcium, chromium, copper, cobalt, tin, rhodium, vanadium, and iron; If the first metal element is the same as the second metal element, the value of b or c is 0.
3. The solid electrolyte according to claim 1, characterized in that The oxide solid electrolyte includes a combination of one or more of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, and lithium lanthanum zirconium titanium oxide; The halogenated metal salt includes a combination of one or more of AlCl3, CaCl2, CrCl5, GaCl3, ZnCl2, MgCl2, and WCl5; The polymerized halogenated metal salt includes a combination of one or more of AlCl3·nH2O, CaCl2·nH2O, CrCl2·nH2O, CuCl2·nH2O, CoCl2·nH2O, SnCl2·nH2O, RhCl2·nH2O, VCl2·nH2O, and FeCl2·nH2O, where 1≦n≦6.
4. A method for preparing a solid electrolyte according to any one of claims 1 to 3, characterized in that: include: Mixing lithium chloride, a metal halide salt, and a polymerized metal halide salt according to a preset molar ratio, and adding the obtained halogenated mixture into a ball mill for ball milling; During the ball milling process, adding the oxide solid electrolyte multiple times at a first preset interval until the mass ratio of the oxide solid electrolyte to the halogenated mixture reaches a preset mass ratio, and the mass of the oxide solid electrolyte added each time is 5% to 15% of the mass of the halogenated mixture; During the ball milling process, the ball milling is stopped every second preset time interval, and the ball mill is kept warm at a preset temperature under an inert gas atmosphere to obtain an electrolyte powder; Pressing the electrolyte powder into a shape to obtain an electrolyte; Etching the electrolyte to a preset depth; The etched electrolyte and the water-absorbing molecular sieve are sintered in a tantalum-containing steam atmosphere in a tubular furnace to obtain a solid electrolyte in which an amorphous non-crystalline halide electrolyte covers the oxide solid electrolyte.
5. The method for preparing a solid electrolyte according to claim 4, characterized in that: The preset molar ratio of the lithium chloride, the metal halide salt, and the polymerized metal halide salt is (1-10): (1-20): 1; The ball-to-material ratio of the ball mill is (10~40) : 1, the ball milling time is 20 min~2400 min, and the ball milling speed is 1 r / min~1000 r / min.
6. The method for preparing a solid electrolyte according to claim 4, characterized in that: The first preset interval time is 10 min~30 min; The preset mass ratio of the oxide solid electrolyte to the halogenated mixture is 10:(0.1-5); The D50 of the oxide solid electrolyte is 700 nm~1500 nm.
7. The method for preparing a solid electrolyte according to claim 4, characterized in that: The second preset interval time is 5 min to 10 min; The preset temperature is 100° C. to 300° C., and the insulation time of the inert gas insulation is 10 min to 60 min.
8. The method for preparing a solid electrolyte according to claim 4, characterized in that: The preset depth is 3nm~7nm.
9. The method for preparing a solid electrolyte according to claim 4, characterized in that: The tantalum-containing vapor includes tantalum pentaiodide vapor or tantalum pentafluoride vapor; The sintering parameters are: sintering temperature is 400°C to 1200°C, and sintering time is 2 h to 24 h.
10. A solid-state lithium battery, characterized in that: The invention comprises the solid electrolyte according to any one of claims 1 to 3, or the solid electrolyte obtained by the preparation method of the solid electrolyte according to any one of claims 4 to 9.
Citation Information
Patent Citations
Composite material and preparation method thereof
CN114436675A
Solid electrolyte material and preparation method and application thereof
CN117497836A
Oxidation halide solid electrolyte composite material, preparation method thereof and battery
CN119400937A
Positive electrode active material layer, positive electrode, and all-solid-state secondary battery
WO2024135845A1
KR20240093239A